2001
DOI: 10.1136/heart.86.4.391
|View full text |Cite
|
Sign up to set email alerts
|

Ten year mortality in subsets of patients with an acute coronary syndrome

Abstract: Objective-To describe the mortality during the subsequent 10 years for subsets of patients hospitalised for suspected acute coronary syndrome. Patients and methods-All patients who were admitted to the emergency department in one hospital during 21 months for chest pain or other symptoms raising suspicion of an acute coronary syndrome were registered. From this baseline population three subgroups were defined among those being hospitalised: patients who developed a Q wave acute myocardial infarction (AMI) (n =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 11 publications
2
12
0
Order By: Relevance
“…8 Of 2 investigations of patients admitted to the ICU or CCU, 1 showed that the number of AMI patients was more than twice that of UA patients, 9 and the other revealed that UA patients outnumbered AMI patients by a ratio of 1.5 to 1. 10 The ratio of UA vs AMI patients obtained in the present study, which involved inpatients only, might be different if those treated as outpatients had been included. Because the largest percentage of UA patients in the case report investigation had Braunwald class III disease, those with Braunwald class I or II disease may have been treated on an outpatient basis.…”
Section: Discussionmentioning
confidence: 99%
“…8 Of 2 investigations of patients admitted to the ICU or CCU, 1 showed that the number of AMI patients was more than twice that of UA patients, 9 and the other revealed that UA patients outnumbered AMI patients by a ratio of 1.5 to 1. 10 The ratio of UA vs AMI patients obtained in the present study, which involved inpatients only, might be different if those treated as outpatients had been included. Because the largest percentage of UA patients in the case report investigation had Braunwald class III disease, those with Braunwald class I or II disease may have been treated on an outpatient basis.…”
Section: Discussionmentioning
confidence: 99%
“…2 The contemporary definition of MI, introduced in 1999 3 and revised in 2007 4 , focused on circulating biomarkers, predominantly troponin, that detect myocardial necrosis with high sensitivity. However, most of the prior studies that investigated long-term outcomes on the basis of MI classification focused on non-Q-wave MI versus Q-wave MI comparisons, [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] whereas fewer contemporary studies have used the newer troponin-based MI definition and classification system (STEMI versus NSTEMI). [21][22][23][24] …”
mentioning
confidence: 99%
“…The study is based on a previously reported decision tree, [20] validated in several external cohorts [8,15,[37][38][39][40] and tailored to the purpose and available data. The model compares two alternative strategies in patients experiencing a first episode of NSTE-ACS pretreated with aspirin, clopidogrel and a glycoprotein IIb/IIIa antagonist and undergoing early coronary catheterization.…”
Section: Decision Modelmentioning
confidence: 99%